The influence of transformational leadership style and situasional leadership on employee job satisfaction in the population and civil registration office of Tangerang Regency - Intan August Vina; Herayati Herayati; Martinus Wahyu Purnomo (Trigin Publisher, 2023)
Transformasional leadership, characterized by the development of a clear vision, providing inspiration, and fostering indivisual growth, is believed to influence employee job satisfaction. Situasional leadership, which adapts leadership styles to different needs and situations, can also play a significant role in creating optimal job satisfaction. The objective of this research is to determine whether transformational and situational leadership styles, either individually or in combination, impact employee job satisfaction in the Department of Population and Civil Registration of Tangerang Regency. This research method collected data through questionnaires from 38 employees in the Department of Population and Civil Registration of Tangerang Regency. The results of the F-test produced an F-value of 61.149. It can be concluded that the calculated F-value of 61.149 is greater than the tabulated F-value of 3.267. Furthermore, in the T-test, the calculated T-value for variable X1 is 5.855, which is greater than the tabulated T-value of 2.030, and the calculated T-value for variable X2 is 2.764, which is also greater than the tabulated T-value of 2.030. Both variable decisions are based on a significance level 0f 0,000, which is smaller than 0,05. It can be concluded that both X1 and X2 have a significant impact on employee job satisfaction. Additionally based on the F-test results, it can be concluded that both variables also have a positive impact on employee job satisfaction with the calculated F-value being greater than the tabulated F-value.